Dyslipidemia and Atherosclerosis - B Setianto (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Dyslipidemia and atherosclerosis are met in the concept of atherogenic dyslipidemia that has .....